2022
DOI: 10.1126/sciadv.abm3689
|View full text |Cite
|
Sign up to set email alerts
|

The stereotype that girls lack talent: A worldwide investigation

Abstract: Recent research has shown that there exist gender stereotypes that portray men as more brilliant or inherently talented than women. We provide a large-scale multinational investigation of these stereotypes and their relationship with other gender gaps. Using a survey question asked to more than 500,000 students in 72 countries, we build a measure of the stereotypes associating talent with men and show that they are present in almost all studied countries. These stereotypes are stronger among high-achieving stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 70 publications
(96 reference statements)
0
22
0
3
Order By: Relevance
“…Adicionalmente a la falta de autoeficacia, las adolescentes que sufren las consecuencias de los estereotipos negativos de género respecto a la programación informática presentan menores niveles de autoeficacia y confianza que los hombres, hecho que empieza en la niñez y aumenta en la adolescencia (Robnett, 2015). Otros estereotipos de género atribuyen mayor talento a los hombres que a las mujeres, (Napp 2022).…”
Section: Discusión Y Conclusionesunclassified
“…Adicionalmente a la falta de autoeficacia, las adolescentes que sufren las consecuencias de los estereotipos negativos de género respecto a la programación informática presentan menores niveles de autoeficacia y confianza que los hombres, hecho que empieza en la niñez y aumenta en la adolescencia (Robnett, 2015). Otros estereotipos de género atribuyen mayor talento a los hombres que a las mujeres, (Napp 2022).…”
Section: Discusión Y Conclusionesunclassified
“…Misogyny is a serious social problem manifested through cultural beliefs that consider women as inferior beings [1], [2], violating the principle of gender equality, a fundamental and inalienable human right [3]. In general, it has been associated with attitudes biased against women, such as male privilege, gender discrimination, sexual objectification, verbal aggressiveness, and physical violence [2].…”
Section: Introductionmentioning
confidence: 99%
“…Although the use of words may differ in social media and music, we argue that misogyny in both is closely related because it derives from sociocultural attitudes that might include biases against women. For example, sexual content and derogatory words (e.g., s**t and b**ch) 1 often have negative connotations for women in both domains.…”
Section: Introductionmentioning
confidence: 99%
“…Lack of role models and recognition, family responsibilities, and inherent biases all have an impact on women's academic development 8 . The higher the academic status, the lower the number of women, which is called “glass ceiling” 9 . Additionally, previous studies have showed that women tend to have lower rates of publication, especially in senior author positions 10 .…”
Section: Introductionmentioning
confidence: 99%
“…8 The higher the academic status, the lower the number of women, which is called "glass ceiling". 9 Additionally, previous studies have showed that women tend to have lower rates of publication, especially in senior author positions. 10 Undeniably, this phenomenon is negative to the improvement of gender imbalance in higher academic positions, arousing concerns about prejudice and obstacles women may encounter in the publishing process.…”
Section: Introductionmentioning
confidence: 99%